FANTASI TOKOH SERIAL MISTERI PEDANG SKINHEALD KARYA ATAKA AWWALLUR RIZQI - Noor Hadi (Madah: Jurnal Bahasa dan Sastra, 2012)
This study is aimed at describing the fantasy of the characters in the children stories entitled Misteri Pedang Skinheald: Sang Pembuka Segel and Misteri Pedang Skinheald II: Awal Petualangan Besar by Ataka Awwallur Rizqi. The subjects of the research were two children stories. They were entitled  Misteri Pedang Skinheald: Sang Pembuka Segel and Misteri Pedang Skinheald II: Aw al Petualangan Besar by Ataka Awwallur Rizqi. The objects of the research were the fantasy  character in both children stories. The study used intrinsic approach. It is an approach applying close reading of the stories with an emphasis on the determinations of the fantasy  character. The analysis was done by making categories, data tabulation, and verbal description. These phases were then continued by making inferences, such as a profound comprehension, a comparison between one inference and the other, and conclusion drawing. The results of the research are as the following: First, the character contains the flat character and round character. Second, there are elements of fantasy which support the story events such as magics, supernatural swords, and supernatural capabilities inside the characterization.